Treatment of colorectal cancer in Sub‐Saharan Africa: Results from a prospective Nigerian hospital registry. Issue 2 (19th November 2019) - Sharma, Avinash; Alatise, Olusegun I.; Adisa, Adewale O.; Arowolo, Olukayode A.; Olasehinde, Olalekan; Famurewa, Olusola C.; Omisore, Adeleye D.; Komolafe, A. O.; Olaofe, O.; Katung, Aba I.; Ibikunle, Ayoola D.; Egberongbe, Ayoola A.; et al.
Abstract: Background: Colorectal cancer (CRC) is the third most common cancer worldwide. Mortality for CRC is improving in high income countries, but in low and middle income countries, rates of disease and death from disease are rising. In Sub‐Saharan Africa, the ratio of CRC mortality to incidence is the highest in the world. This study investigated the nature of CRC treatment currently being offered and received in Nigeria. Methods: Between April 2013 and October 2017, a prospective study of consecutively diagnosed cases of CRC was conducted. Patient demographics, clinical features, and treatment recommended and received was recorded for each case. Patients were followed during the study period every 3 months or until death. Results: Three hundred patients were included in our analysis. Seventy‐one percent of patients received a recommended surgical operation. Of those that didn't undergo surgery as recommended, 37% cited cost as the main reason, 30% declined due to personal reasons, and less than 5% absconded or were lost to follow up. Approximately half of patients (50.5%) received a chemotherapy regimen when it was recommended, and 4.1% received radiotherapy when this was advised as optimal treatment. With therapy, the median overall survival for patients diagnosed with stage III and stage IV CRC was 24 and 10.5 months respectively. Overall, we found significantly better median survival for patients that received the recommended treatment (25 vs 7 months;  P  < .01). Conclusions: A number of patients were unable to receive the recommended treatment, reflecting some of the burden of untreated CRC in the region. Receiving the recommended treatment was associated with a significant difference in outcome. Improved healthcare financing, literacy, training, access, and a better understanding of tumor biology will be necessary to address this discrepancy.